The issues of justice in economic and environmental policy - Kazimierz Górka; Agnieszka Thier (Central European Economic Journal (CEEJ), 2021)
The article presents the gist, the kinds and manifestations of justice, with the discussion of the controversies around social justice. The analysis deals with the relationship between social justice and economic efficiency and effectiveness - especially in the environmental protection - as well as the concepts of international and cross-generational justice. In summary, the authors discussed inequality of income and the structure of welfare benefits as well as the scale of poverty and social exclusion in Poland.
Keywords: D63; E24; Q57; 330; cross-generational justice; economic effectiveness versus economic efficiency; income differentiation; social justice; social exclusion